2007
DOI: 10.1590/s0100-29452007000100027
|View full text |Cite
|
Sign up to set email alerts
|

Variabilidade genética de acessos silvestres e comerciais de Passiflora edulis Sims. com base em marcadores RAPD

Abstract: GENETIC VARIABILITY OF WILD AND COMMERCIAL PASSION FRUIT (Passiflora edulis Sims.) ACCESSIONS USING RAPD MARKERSABSTRACT -There are a great diversity of colors, sizes and aromas of fruits in wild accessions of P. edulis in Brazilian Savannah. These accessions are also important resistance sources against illness which can be incorpored in passionfruit breeding programs. In this work, the objetive was to evaluate the genetic variability in wild and commercial P. edulis accessions using RAPD markers. The genomic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
28
0
6

Year Published

2008
2008
2018
2018

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 40 publications
(34 citation statements)
references
References 4 publications
0
28
0
6
Order By: Relevance
“…A possible explanation for this result could rely on the involvement of wild species of Passiflora in the genealogy of this hybrid. In a similar study, BELLON et al (2007) analyzing commercial and wild accessions of P. edulis verified that mostly, the wild accessions were responsible for the amplification of the genetic basis. Clustering of the two accessions of P. alata, used as outgroup is common to occur between related genotypes (AUKAR et al, 2002).…”
Section: Resultsmentioning
confidence: 78%
See 1 more Smart Citation
“…A possible explanation for this result could rely on the involvement of wild species of Passiflora in the genealogy of this hybrid. In a similar study, BELLON et al (2007) analyzing commercial and wild accessions of P. edulis verified that mostly, the wild accessions were responsible for the amplification of the genetic basis. Clustering of the two accessions of P. alata, used as outgroup is common to occur between related genotypes (AUKAR et al, 2002).…”
Section: Resultsmentioning
confidence: 78%
“…Brazil is known as a diversity center of passion fruit, and possessing a wide genetic variability of Passiflora, which is the starting point for genetic breeding programs (GANGA et al, 2004). As revised by BELLON et al (2007), due to market advantages for the pulp industry and spread consumption, genotypes of Passiflora edulis Sims. have been employed by breeding programs in Brazil and Australia.…”
Section: Introductionmentioning
confidence: 99%
“…The P. edulis genotypes used in this study were originated from openpollinated genotypes of field production, and despite indirectly, they were the result of participatory plant breeding or local selections performed by the producers themselves. On the other hand, Bellon et al (2007) and Bellon et al (2009) assessed plants from wild and commercial accessions together, contributing to a greater variability between members of the population.…”
Section: Resultsmentioning
confidence: 99%
“…Although preliminary analyses have signaled this possibility (Sánchez et al, 1999), analyses of a higher number of materials showed some similarity between different accesses of P. edulis, also as a consequence of the place of origin of each material, and breeding work (Bellon et al, 2007). However, none of these aspects, isolatedly, (color of the fruit, geographical proximity, or breeding) allows the recognition of any group within the species P. edulis, because, genetically, there are purple passion fruits that show stronger similarity with yellow passion fruits than with other yellow passion fruits; Brazilian materials that show stronger similarity with Australian materials than with some Brazilian materials; and native materials that show stronger similarity with improved materials than with other native materials (Bellon et al, 2007). In other words, it is not possible to classify all the variability observed in P. edulis into just two groups.…”
Section: Colors Of the Sour Passion Fruitmentioning
confidence: 99%